Additive manufacturing of metallic glasses and high-entropy alloys: Significance, unsettled issues, and future directions. (20th March 2023) - Liu, Haishun; Yang, Dengfeng; Jiang, Qi; Jiang, Yangyang; Yang, Weiming; Liu, Lin; Zhang, Lai-Chang
Highlights: A comprehensive, systematic, and timely review on the AM of MGs and HEAs is conducted. MGs and HEAs fabricated by various AM techniques including SLM, EBM, DED, etc. are compared. Strategies to improve the quality of printed MGs and HEAs are suggested. Unsettled issues and future research interests on the AM of MGs and HEAs are identified. Abstract: As two kinds of well-known prominent high-performance alloys, metallic glasses (MGs) and high-entropy alloys (HEAs) have attracted increasing attention. Most of them contain multiple alloying components, demonstrate intriguing microstructures, and exhibit excellent properties; however, their unique performances are closely dependent on the fabrication process, although they are limited due to the need for rapid solidification during fabrication. On the other hand, additive manufacturing (AM) can be used to fabricate complex parts via rapid solidification, thus saving materials. These advantages provide AM with a great possibility to produce MG and HEA materials with tunable microstructures therefore properties, and corresponding parts with complex geometries, large dimensions, and more functions. This paper provides a comprehensive and systematic overview of the manufacturing and properties of MGs and HEAs using AM techniques. The correlation between MGs and HEAs with conventional manufacturing methods and the difficulties encountered are retrospectively discussed. Afterward, this review specifically focuses on the recent research advances in MGs and HEAs fabricated using AM technologies. Then, various properties of the AM-fabricated MGs and HEAs are discussed. Finally, the remaining issues and potential solutions, challenges, and future directions on the AM of MGs and HEAs are also presented.